Linguacognitive analysis of the concept of “Peace” through color imagery in The Old Man and the Sea - Usmonova, Zarina Habibovna; Rakhmonova, Jasmina Anvarovna; Farkhodova, Dilnoza Uktamovna (The Lingua Spectrum, 2026)
This article presents a comprehensive linguacognitive analysis of the concept of peace in Ernest Hemingway’s The Old Man and the Sea (1952). The study examines how color imagery – particularly the chromatic registers of blue and white – functions as a cognitive mechanism for structuring the protagonist Santiago’s perception of existential harmony. Drawing on conceptual metaphor theory as developed by Lakoff and Johnson (1980), and subsequently extended by Kövecses (2010), the research argues that peace in Hemingway’s narrative is not a passive condition but an active process of internal alignment between self, struggle, and nature. Through semantic, contextual, and metaphorical analysis of selected passages, the article demonstrates that blue encodes depth, continuity, and unity with the natural world, while white signifies purification, resolution, and transcendence beyond material defeat. The findings contribute to interdisciplinary research at the intersection of cognitive linguistics, literary studies, and cultural semantics.